An International Overview of Certified Practices in Creative Tourism in Rural and Urban Territories. (November 2022) - Remoaldo, Paula; Matos, Olga; Freitas, Isabel; Gôja, Ricardo; Araújo Alves, Juliana; Ribeiro, Vítor; Pereira, Miguel; Xavier, Carla
A large number of destinations have been experimenting a changeover from the current massified cultural tourism to a creative tourism model. In this new model of tourism, urban territories have been privileged by its implementation, and in the past 20 years, urban studies on cultural and creative industries and initiatives have been taking place in large cities marginalizing small-sized cities and specifically rural areas. This article envisages assessing the differences between rural and urban institutions/platforms, mainly certified by the Creative Tourism Network, in what concerns the practices and offers in creative tourism worldwide. A database of 20 items was organized and a typology was used to categorize the type of territory of intervention for each institution. A total of 24 institutions from several countries were surveyed and a qualitative analysis was done and supported by the narratives of their leaders. Urban areas revealed to have a more active and diverse creative tourism activities. The results provide the need for more consolidated communication strategies and partnerships for these activities to become economically more sustainable. In addition, this research provides researchers and practitioners relevant information of how creative tourism is developed in rural and urban territories, the gaps and lack of information, and all the possible directions toward the development of the creative tourism industry.